GENERALIZED TETANUS OF MODERATE SEVERITY FOLLOWING A RUSTY NAIL INJURY: A CASE REPORT - andi ridwan jalal; apriani aridan (Al-Iqra Medical Journal : Jurnal Berkala Ilmiah Kedokteran, 2026)
Introduction: Tetanus is an acute infectious disease caused by Clostridium tetani, characterized by muscle rigidity and spasms. Case Presentation: We report the case of a 9-year-old boy who presented with generalized body stiffness, difficulty opening his mouth, and seizures triggered by sound and movement. Two days before the onset of symptoms, the patient sustained a puncture wound from a rusty nail without receiving adequate medical treatment. Physical examination revealed trismus, risus sardonicus, generalized muscle rigidity, and reflex spasms. The diagnosis was established based on the patient’s clinical presentation and classified as moderate tetanus using the Ablett, Phillips, and Dakar scoring systems. The patient was treated with intravenous metronidazole, tetanus immunoglobulin, diazepam, supportive therapy, and intensive care unit management. Conclusion: This case highlights the importance of early diagnosis and prompt comprehensive management in reducing tetanus-related morbidity and mortality.